Determination of low methylmercury concentrations in peat soil samples by isotope dilution GC-ICP-MS using distillation and solvent extraction methods. (April 2015) - Pietilä, Heidi; Perämäki, Paavo; Piispanen, Juha; Starr, Mike; Nieminen, Tiina; Kantola, Marjatta; Ukonmaanaho, Liisa
Highlights: MeHg concentrations in peat soil samples were determined by isotope dilution PT-GC-ICP-MS. MeHg was separated with N2 -assisted distillation and acidic KBr/CuSO4 solvent extraction. The obtained MeHg concentrations were similar with the two separation methods used. Distillation method is fast and needs no the use of toxic organic solvents. MeHg concentrations in peat soil samples varied from 0.8 to 18 μg kg −1 (dry weight). Abstract: Most often, only total mercury concentrations in soil samples are determined in environmental studies. However, the determination of extremely toxic methylmercury (MeHg) in addition to the total mercury is critical to understand the biogeochemistry of mercury in the environment. In this study, N2 -assisted distillation and acidic KBr/CuSO4 solvent extraction methods were applied to isolate MeHg from wet peat soil samples collected from boreal forest catchments. Determination of MeHg was performed using a purge and trap GC-ICP-MS technique with a species-specific isotope dilution quantification. Distillation is known to be more prone to artificial MeHg formation compared to solvent extraction which may result in the erroneous MeHg results, especially with samples containing high amounts of inorganic mercury. However, methylation of inorganic mercury during the distillation step had no effect on the reliability of the final MeHg results when natural peat soil samples were distilled. MeHg concentrations determined in peat soil samples after distillation were compared to those determined after the solvent extraction method. MeHg concentrations in peat soil samples varied from 0.8 to 18 μg kg −1 (dry weight) and the results obtained with the two different methods did not differ significantly ( p = 0.05). The distillation method with an isotope dilution GC-ICP-MS was shown to be a reliable method for the determination of low MeHg concentrations in unpolluted soil samples. Furthermore, the distillation method is solvent-free and less time-consuming and labor-intensive when compared to the solvent extraction method.